The severity and dynamics of changes in the serum concentration of biochemical markers of muscle tissue damage in an experienced ultramarathon runner after overcoming a distance of 165 km against the background of continuing physical activity - E. N. Bezuglov; M. S. Shoshorina; O. B. Talibov (National Electronic Information Consortium (NEICON), 2023)
Purpose: to determine the severity and dynamics of changes in the concentration of biochemical markers of muscle tissue damage in the blood serum of an experienced ultramarathon runner after overcoming a distance of 165 kilometers.Materials and methods: measurement of serum concentrations of markers of muscle tissue damage (aspartate aminotransferase (AST), alanine aminotransferase (ALT), creatine kinase (CK), creatine kinase MB (CK-MB), myoglobin) in serum before and 16 and 144 hours after ultramarathon in an experienced runner (age 36, height 186 cm, weight 76 kg, body mass index 21.96).Results: 16 hours after the end of the race, extremely high levels of AST, ALT, CK, CK-MB and myoglobin were observed, the combination of which indicates severe rhabdomyolysis. After 144 hours, a decrease in the level of all markers of muscle tissue damage, including myoglobin, was noted, however, they continued to remain significantly higher than the reference values. At the same time, the athlete did not have any significant pathological symptoms, and he continued to train in the recovery mode.Conclusion: ultramarathon races lead to significant muscle damage, which can lead to rhabdomyolysis. Its severity may not correlate with any significant clinical manifestations.